Metamorphosis of Mining Landscapes in the Lower Lusatian Lignite Basin (Germany): New Uses and New Image of a Mining Region - Michel Deshaies (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Since German reunification, the landscapes of the East German lignite basins, which have been shaped by open-cast mining, have undergone a profound transformation as a result of the closure of most of the mines. Many large lakes have been created in the old pits to support the development of new tourism activities. Huge mining wasteland areas have been reforested or used to install wind farms and photovoltaic parks. These developments have been encouraged by the creation of an International Architecture Exhibition (IBA Fürst Pückler Land) to promote the idea of social renewal through the construction of new landscapes. These projects, supported by private investors, have given a new image and new values to landscapes that exist as a result of mining. This article analyses the process of transforming mining landscapes into post-mining landscapes characterised by the importance of lakes and second-hand nature, as well as by the enhancement of industrial heritage and the development of renewable energy.